Curtailing the spread of COVID-19 in Nigeria using digital framework and data driven approaches - Bolanle Adefowoke Ojokoh; Benjamin S. Aribisala; Oluwafemi A. Sarumi; Tobore V. Igbe; Abimbola H. Afolayan; Arome J. Gabriel; Abiola Ezekiel Taiwo; Olatunji M. Omisore; Uchechukwu M. Chukwuocha; Olusola T. Babalola; Tolulope A. Adebayo (EngMedicine)
The onset of the coronavirus disease 2019 (COVID-19) pandemic had profound economic and societal repercussions worldwide. Some nations managed to mitigate the spread of the virus sufficiently early through implementing digital frameworks and other containment measures. However, many countries in Africa faced significant challenges due to limited technological infrastructure for infection control. This study investigated the efficacy of digital frameworks, with a specific focus on contact tracing apps, in stemming the spread of COVID-19 within Nigeria. It investigated the potential impact of the use of these apps on reducing infection rates and improving public health strategies. Additionally, this study provided insights into the practical implementation of such frameworks and the challenges associated with their nationwide deployment. A structured user-oriented questionnaire was distributed to participants across different geopolitical zones in Nigeria. The study employed association rule mining and descriptive statistics, setting a support threshold of 0.001 and confidence of 0.8, to uncover patterns of interest among respondents. Cluster analysis using Barnes–Hut t-Distributed Stochastic Neighbor Embedding was conducted to derive reliable inferences from the data. The findings revealed adoption rates of 69.7% and 93.8% for the minimum and maximum, respectively, in favor of using a COVID-19 contact tracing app. Furthermore, 71.6% of participants expressed concerns about the privacy of their personal information, whereas 74% showed an interest in receiving daily reports on estimated COVID-19 infection in their communities. This study presents empirical evidence highlighting the potential of contact tracing apps as valuable tools for monitoring and curbing the spread of COVID-19 and related diseases in Nigeria.